Human Identity as a Cultural and Biological Construction - Jurić, Hrvoje, filozof (Array, 2010)
Regarding the recent advances in the field of science and technology – primarily within information and communication technology, and biotechnology – human as an individual and humankind altogether are facing challenges of a new kind, while the problems of personal and human identity are becoming more complex than ever. Old questions about identity, e.g. "Who am I?", "Who are we?", "Who (or what) is human?", "What I/we should (or want to) be?" have to be asked in some new contexts. We must not be infatuated by the emancipatory potential of modern technoscience to the extent of not asking questions about new types of representation, manipulation or even enslavement of the human and the humankind. Moreover, we must go beyond the boundaries of the human – we must extend the old ethical and socio-political questions over into the field of bioethics or transhumanist ethics (cyborg ethics, animal ethics, ecoethics, cosmoethics). However, the epistemic barycentre is still in the sphere of the human. Therefore we need to investigate where and what the human is on the crucifix of the identity which endpoints are: being a (distinctive) person and being a (human) being, (visible) embodiment and (invisible) genetic constitution. On this basis we should pose the question on the relationship between traditional cultural and contemporary biological construction of human identity.